Cover Image, Volume 93, Issue 10. Issue 10 (7th September 2018) - Wang, Guanhua; Xia, Yue; Liang, Benke; Sui, Wenjie; Si, Chuanling
Abstract : The cover image, by Guanhua Wang et al., is based on the Research Article Successive ethanol‐water fractionation of enzymatic hydrolysis lignin to concentrate its antimicrobial activity, DOI:10.1002/jctb.5656 . Abstract : The cover image, by Guanhua Wang et al., is based on the Research Article Successive ethanol‐water fractionation of enzymatic hydrolysis lignin to concentrate its antimicrobial activity, DOI:10.1002/jctb.5656 .